2007
DOI: 10.1099/jmm.0.46964-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically similar isolates of Klebsiella pneumoniae serotype K1 causing liver abscesses in three continents

Abstract: The magA gene was sought in hypermucoviscous isolates of Klebsiella spp., the Klebsiella K serotype reference strains and in isolates of the K1 serotype of Klebsiella pneumoniae from the UK, Hong Kong, Israel, Taiwan and Australia. Only K1 isolates were PCR positive for magA; this gene was found in all such isolates tested. Hypermucoviscosity was not confined to magA positive isolates, nor was it found in all magA positive isolates. Comparison of XbaI PFGE profiles revealed that most (19/23) of the magA positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 13 publications
12
117
1
1
Order By: Relevance
“…One study characterizing HV K. pneumoniae strains isolated from 4 different continents found that these strains were almost exclusively K1 strains (93%), while the remaining minority were K2 strains (235), a finding consistent with results of previous studies (18,(236)(237)(238)(239)(240)(241). Interestingly, in one study, 27/28 of the K1 HV K. pneumoniae isolates belonged to the same clonal complex (CC23), while the two K2 HV strains examined were genetically unrelated and arose from two distinct clonal lineages (ST25 and ST86) (235).…”
Section: Capsulesupporting
confidence: 81%
“…One study characterizing HV K. pneumoniae strains isolated from 4 different continents found that these strains were almost exclusively K1 strains (93%), while the remaining minority were K2 strains (235), a finding consistent with results of previous studies (18,(236)(237)(238)(239)(240)(241). Interestingly, in one study, 27/28 of the K1 HV K. pneumoniae isolates belonged to the same clonal complex (CC23), while the two K2 HV strains examined were genetically unrelated and arose from two distinct clonal lineages (ST25 and ST86) (235).…”
Section: Capsulesupporting
confidence: 81%
“…S7A). The bestknown virulent K. pneumoniae clone is ST23, which is able to cause severe disease in apparently healthy individuals (13,54) and typically carries all four acquired siderophore systems as well as rmpA and rmpA2. The 13 ST23 isolates in our collection were isolated from invasive infections more frequently than were other KpI (69% of ST23 were invasive vs. 35% of other KpI; OR 4.4, P = 0.01; Fisher's exact test) and were associated solely with CA infections.…”
Section: Resultsmentioning
confidence: 99%
“…Other important virulence factors in these Klebsiella strains include the rmpA gene, which regulates synthesis of the capsule, and aerobactin, a catecholate siderophore (9)(10)(11)(12). Despite numerous reports confirming the association of this distinctive clinical presentation with K. pneumoniae K1 in Asia, descriptions of K1-associated pyogenic abscesses with ophthalmologic complications originating outside this region are less frequent (5,13).…”
mentioning
confidence: 94%